2010
DOI: 10.1038/nchembio.347
|View full text |Cite
|
Sign up to set email alerts
|

The role of conformational entropy in molecular recognition by calmodulin

Abstract: The physical basis for high affinity interactions involving proteins is complex and potentially involves a range of energetic contributions. Among these are changes in protein conformational entropy, which cannot yet be reliably computed from molecular structures. We have recently employed changes in conformational dynamics as a proxy for changes in conformational entropy of calmodulin upon association with domains from regulated proteins. The apparent change in conformational entropy was linearly related to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
345
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(367 citation statements)
references
References 51 publications
(91 reference statements)
22
345
0
Order By: Relevance
“…The effects of myristoylation in hisactophilin are similar to results for other proteins where regions of increased local stability are counterbalanced by regions of decreased local stability implicated in function regulation by ligand binding (29)(30)(31). The folding energetics and mechanism for myristoylated hisactophilin support the notion that local energetic frustration and the accumulation of strain during switching can be linked to function as observed in allosteric proteins (16) and for functional and/or hydrophobic residues in other proteins (7,11,32,33).…”
Section: Discussionsupporting
confidence: 63%
“…The effects of myristoylation in hisactophilin are similar to results for other proteins where regions of increased local stability are counterbalanced by regions of decreased local stability implicated in function regulation by ligand binding (29)(30)(31). The folding energetics and mechanism for myristoylated hisactophilin support the notion that local energetic frustration and the accumulation of strain during switching can be linked to function as observed in allosteric proteins (16) and for functional and/or hydrophobic residues in other proteins (7,11,32,33).…”
Section: Discussionsupporting
confidence: 63%
“…Although our data identify the C-terminal segment of PAPR as the primary molecular determinant for favorable binding entropy, our next goal was to better define the nature of this contribution. Total binding entropy (ΔS total ) obtained from ITC measurement of protein-protein interactions is a complex term, but can be simplified as a sum of changes in the solvation entropy (ΔS sol ), protein translational and rotational entropy (ΔS RT ) and protein conformational entropy (ΔS conf ) (28). Although accurate quantitative dissection of ΔS tot into contributions from ΔS sol , ΔS RT , and ΔS conf is difficult and often controversial, some initial insight can be obtained by combining inputs from experimental measurements and theoretical models.…”
Section: Conformational Restriction Of Oxidized Papr Is Essential Formentioning
confidence: 99%
“…In fact, empirical calibration of the NMR-derived conformational entropy suggested that the standard approach of summing up the individual contribution of each one of the experimentally accessible bond vectors may in fact underestimate the overall contribution of conformational entropy to the binding free energy. 61 The emerging view of protein flexibility as a major source of conformational entropy that can influence the thermodynamics of binding, also supported by many other examples, 8,36 indicates that dynamic activation of protein function may be more common than thought. …”
Section: Dynamic Activation Of Protein Functionmentioning
confidence: 99%
“…Very interesting results on calmodulin have been particularly revealing about the role of conformational entropy in molecular recognition and allostery. 60,61 Calmodulin, a central player in calcium-mediated signaling, has been used as a model system to investigate the role of changes in fast (subnanosecond) internal dynamics and its associated conformational entropy in protein-ligand binding. By studying calmodulin in complex with a series of different binding peptides, it was found that the apparent change in conformational entropy was linearly related to the change in the overall binding entropy.…”
Section: Dynamic Activation Of Protein Functionmentioning
confidence: 99%